Injection molding of thermoplastics microfluidic device - Muhammad Ridwan Mohd Idris (2015)
Microfluidic devices have been around since the 1980s. They are used for researches in many different fields, ranging from engineering to biotechnology. As such, the demand for microfluidic devices is ever-growing. Many ways are then being explored to facilitate the fabrication of these devices in the shortest time possible. As a result, injection molding becomes the widely-chosen method to make these thermoplastic microfluidic devices due to its ability to rapidly produce parts in large quantities. One of the major concerns of microfluidic devices is the presence of molded-in residual stress. It has an effect on the microchannels deformation during the thermal bonding process. Therefore, the author will explore how the molding parameters affect the molded-in residual stress with the study focusing on holding temperature and cooling temperature of the injection molding process.